Comparative transcriptome investigation of global gene expression changes caused by miR156 overexpression in Medicago sativa. (December 2016) - Gao, Ruimin; Austin, Ryan; Amyot, Lisa; Hannoufa, Abdelali
Abstract Background Medicago sativa (alfalfa) is a low-input forage and potential bioenergy crop, and improving its yield and quality has always been a focus of the alfalfa breeding industry. Transgenic alfalfa plants overexpressing a precursor of alfalfamicroRNA156 (MsmiR156 ) were recently generated by our group. These plants (miR156OE) showed enhanced biomass yield, reduced internodal length, increased shoot branching and trichome density, and a delay in flowering time. Transcripts of threeSQUAMOSA-PROMOTER BINDING PROTEIN-LIKE (SPL) genes (MsSPL6, MsSPL12, andMsSPL13 ) were found to be targeted for cleavage byMsmiR156 in alfalfa. Results To further illustrate the molecular mechanisms underlying the effects of miR156 in alfalfa, two miR156OE genotypes (A11a and A17) were subjected to Next Generation RNA Sequencing with Illumina HiSeq. More than 1.11 billion clean reads were obtained from our available sequenced samples. A total of 160, 472 transcripts were generated using Trinityde novo assembly and 4, 985 significantly differentially expressed genes were detected in miR156OE plants A11a and A17 using theMedicago truncatula genome as reference. A total of 17 genes (including upregulated, downregulated, and unchanged) were selected for quantitative real-time PCR (qRT-PCR) validation, which showed that gene expression levels were largely consistent between qRT-PCR and RNA-Seq data. In addition to the establishedSPL genesMsSPL6, MsSPL12 andMsSPL13, four newSPLs; MsSPL2, MsSPL3, MsSPL4 andMsSPL9 were also down-regulated significantly in both miR156OE plants. These sevenSPL genes belong to genes phylogeny clades VI, IV, VIII, V and VII, which have been reported to be targeted bymiR156 inArabidopsis thaliana . The gene ontology terms characterized electron transporter, starch synthase activity, sucrose transport, sucrose-phosphate synthase activity, chitin binding, sexual reproduction, flavonoid biosynthesis and lignin catabolism correlate well to the phenotypes of miR156OE alfalfa plants. Conclusions This is the first report of changes in global gene expression in response to miR156 overexpression in alfalfa. The discovered miR156-targetedSPL genes belonging to different clades indicate miR156 plays fundamental and multifunctional roles in regulating alfalfa plant development.